2020
DOI: 10.1590/1806-9282.66.4.485
|View full text |Cite
|
Sign up to set email alerts
|

Family planning among female medical students: are their plans comparable to other professionals?

Abstract: SUMMARY INTRODUCTION Late pregnancy is a problem among physicians, especially surgeons. This paper studies family planning among Medical Students (MS) and Law students (LS). METHODS A questionnaire was sent to all female MS and LS attending the two last years of University in the first semester of 2019. Data on age, family income, marital status, and family planning (age, planning for future pregnancies, timing, professional relationship or other issues, the ideal moment for a pregnancy, attitude tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
4
0
2
Order By: Relevance
“…4 Among 96 of 183 women first-year (2019) medical students at Federal Fluminense University in Rio de Janeiro, Brazil, responding to a survey, two had children, 2%. 5 Among U.S. medical students graduating in 2020, the percentage with dependents was 7%. 1 The fact that these percentages represent thousands of students and indicates the value of systematic study of what items to include in pregnancy and parental leave policies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Among 96 of 183 women first-year (2019) medical students at Federal Fluminense University in Rio de Janeiro, Brazil, responding to a survey, two had children, 2%. 5 Among U.S. medical students graduating in 2020, the percentage with dependents was 7%. 1 The fact that these percentages represent thousands of students and indicates the value of systematic study of what items to include in pregnancy and parental leave policies.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, they are scientifically useful. The basis for our hypothesis was limited citation of the earlier survey study 4 , 5 despite calls for precisely this information. 3 If the hypotheses were supported, adding these items to schools' public websites would be an easily actionable intervention to help current and future students who are parents or are considering parenthood.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research in Brazil comparing female medical and law students (equal prestige careers and similar social backgrounds) detected that only 10-15% showed no interest in getting pregnant in both careers but for different reasons; while medical students prioritized their careers and thought that maternity would impair their professional future, law students gave up maternity to privilege personal life projects. This paper also showed that medical students were older, an important difference when added to the need for postgraduation training, especially for those intending to become surgeons [10].…”
Section: Discussionmentioning
confidence: 82%
“…Nossos resultados demonstram que, apesar de estudos indicarem uma tendência ao adiamento da maternidade/ paternidade em função de um projeto de vida orientado para o acadêmico e o profissional (por exemplo: busca por estabilidade financeira e consolidação da carreira no mercado de trabalho) [16][17][18][19] , há uma percepção hegemônica entre os participantes em relação ao orgulho e à clareza de suas escolhas. Nesse contexto, apesar de os nossos resultados não apresentarem diferenças significativas nas percepções entre homens e mulheres, um estudo realizado em três cursos médicos suíços demonstrou que as mulheres médicas apresentam, em geral, menores índices de empregabilidade e possuem qualificações menos avançadas, ao mesmo tempo que apresentam um estilo de vida mais direcionado aos aspectos relacionados à maternidade 20 .…”
Section: Discussionunclassified